Changes in alcohol consumption during the COVID-19 pandemic: a longitudinal cohort study using smart-breathalyzer data - Houston, Parker D.; Vittinghoff, Eric; Marcus, Gregory M. (Scientific reports, 2024)
Previous studies relying on alcohol sales, alcohol-related injuries, and surveys have suggested that alcohol consumption increased during the COVID-19 pandemic. We sought to leverage over 1 million Breath Alcohol Concentration (BrAC) measurements from Bluetooth-enabled breathalyzers to conduct an objective and longitudinal assessment of alcohol use during the pandemic. Serial BrAC measurements revealed a decrease in drinking between January 1, 2020 and March 30, 2020, an increase between March 30, 2020 and May 25, 2020, a statistically insignificant decrease between May 25, 2020 and January 1, 2021, and an increase again between January 1, 2021 and June 4, 2021. No statistically significant relationships between shelter-in-place orders and alcohol consumption were detected. These findings demonstrate the complex relationship between the pandemic and alcohol consumption patterns, providing insights that may be relevant to the use of this commonly consumed substance with implications relevant to long-term effects from the patterns observed.